The Influence Of Competence And Physical Work Environment On Employee Work Productivity (Survey of BPR Artha Galunggung Tasikmalaya Employees) - Zaky, Dhiya Fauzan; Arga Sutrisna; Ai Kusmiati Asyiah (Journal of Management, Economic, and Accounting, 2025)
This research aims to determine and analyze the influence of competence and the physical work environment, both simultaneously and partially, on employee work productivity at BPR Artha Galunggung Tasikmalaya. The method used in this research is a survey. With a research sample of 35 employees as respondents. The data used is primary and secondary data. The data analysis tool used in this research is multiple linear regression using the SPSS support application version.25. The test results show that simultaneously the variables used in the research, namely competency and the physical work environment, have a significant effect on employee work productivity at BPR Artha Galunggung Tasikmalaya. Likewise, partially there is a significant influence of competence on employee work productivity, and there is a significant influence of the physical work environment on employee work productivity at BPR Artha Galunggung Tasikmalaya.